2015
DOI: 10.1111/age.12267
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide copy number profiling using high-density SNP array in chickens

Abstract: Phenotypic diversity is a direct consequence resulting mainly from the impact of underlying genetic variation, and recent studies have shown that copy number variation (CNV) is emerging as an important contributor to both phenotypic variability and disease susceptibility. Herein, we performed a genome-wide CNV scan in 96 chickens from 12 diversified breeds, benefiting from the high-density Affymetrix 600 K SNP arrays. We identified a total of 231 autosomal CNV regions (CNVRs) encompassing 5.41 Mb of the chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
6
20
1
Order By: Relevance
“…We observed that CNVRs gain were more abundant than losses in the three types of CNVRs in both populations, in agreement with previous studies (JIA et al, 2013;WANG et al, 2012;YI et al, 2015). Conrad et al (2006) reported that duplicated events are more likely to be maintained than deletions, because deletion CNVRs were relatively gene-poor and therefore these genes were subject to purifying selection.…”
Section: Copy Number Variation In the Chicken Genomesupporting
confidence: 92%
See 3 more Smart Citations
“…We observed that CNVRs gain were more abundant than losses in the three types of CNVRs in both populations, in agreement with previous studies (JIA et al, 2013;WANG et al, 2012;YI et al, 2015). Conrad et al (2006) reported that duplicated events are more likely to be maintained than deletions, because deletion CNVRs were relatively gene-poor and therefore these genes were subject to purifying selection.…”
Section: Copy Number Variation In the Chicken Genomesupporting
confidence: 92%
“…Most of the previous studies were performed on galGal3.0 (ABERNATHY et al, CROOIJMANS et al, 2013;FAN et al, 2013;LUO et al, 2013;TIAN et al, 2013;WANG et al, 2010WANG et al, , 2012. A few recent studies were performed on galGal4.0 (GORLA et al, 2017;YAN et al, 2015;YI et al, 2014YI et al, , 2015, but to date only our study was performed on the most recent version of the genome (galGal5.0). Therefore, we converted the CNVRs identified in galGal3.0 in some studies to galGal4.0 by CrossMap tool (version 0.2.5) (ZHAO et al, 2014) and we repeated the entire CNV calling analyses performed in our study using the galGal4.0.…”
Section: Qtl Overlap and Gene Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the rst two genome-wide scans for CNVs in human genome [7,8], an large number of CNV detection studies have been performed, which revealed that CNVs are ubiquitously distributed in the genome and can in uence the phenotype via regulations of gene expression and gene dosage [9][10][11]. Besides, numerous studies in other species have also shown that CNVs contributed to phenotypic variation of complex diseases and traits [12][13][14][15][16][17][18][19], including MD in chicken [20][21][22]. Two major traditional platforms employed in CNV detection are based on SNP chips, one is known as comparative genomic hybridization (CGH) array, and the other is SNP genotyping array.…”
Section: Introductionmentioning
confidence: 99%